"Double dynamical" take-off technique theory and experiments research of Fosbury flop high jump - Lu, Y.; Su, B.; Tian, F. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The take-off technique of Fosbury flop high jump is "double dynamical" take-off. At the last step take-off phase in run up alone the arc, for the inertia of run up and the athletes body change from inner incline to upright, the body gravity not depress instead of hoist. creative the advantage for the change the direction movement of body gravity and cumulating of upright velocity.the faster of take-off speed at run up alone the arc, the faster of the body gravity raising speed and range when the body gravity change from inner incline to upright. the raising upright speed is accelerate at the body gravity raising phase.